Pemanfaatan media sosial TikTok sebagai platform pemasaran digital pada akun @dododots.by.zen - Arnetta, Devinna Agus Putri; Haryono, Cosmas Gatot (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study aims to analyze the use of TikTok as a digital marketing platform by @dododots.by.zen, a reseller of acne patch products. Originally a short video entertainment platform, TikTok has evolved into a powerful tool for interactive marketing, especially among younger generations. Employing a qualitative descriptive method and a case study approach, the research collected data through interviews and documentation. The findings indicate that the account applies an organic content strategy that is light, educational, and emotionally engaging to increase audience interaction. Its success in reaching the target market is driven by relatable narratives, appealing visual presentation, and the strategic use of trending features. Moreover, the brand’s adaptability to TikTok’s algorithm and user preferences ensures sustained relevance and visibility. The study concludes that TikTok serves as an effective medium for brand building and consumer loyalty, particularly among Gen Z, by emphasizing authentic content, community engagement, and emotional storytelling.